Underlying motivations for rule-violation among juvenile delinquents: A lab-in-the-field experiment - Lubomir Cingl; Vaclav Korbel (Charles University in Prague, Institute of Economic Studies (IES), 2018)
This paper reports on a lab-in-the-field experiment that investigates differences in rule-violating behavior between the inmates of juvenile detention centers and regular adolescents from primary schools of similar age in response to three specific contexts: (i) when they interact with ingroup and outgroup members, (ii) when they are exposed to an unfair economic situation and (iii) when the rule-violating behavior is exposed to others. Our results show substantial similarities between the delinquents and non-problematic adolescents. Even though the juvenile delinquents violate rules more, we find no evidence of ingroup favoritism. Moreover, both groups care similarly about their social image and do not violate rules substantially more after the unfair treatment. Our findings thus show that juvenile delinquents are not inherently different from non-problematic adolescents and highlight the importance of social values for successful resocialization.
Keywords: C93; I21; J13; 330; delinquency; adolescence; rule-violation; experiment; random allocation game